2017
DOI: 10.1186/s13071-017-2548-z
|View full text |Cite
|
Sign up to set email alerts
|

Household knowledge and practices concerning malaria and indoor residual spraying in an endemic area earmarked for malaria elimination in Iran

Abstract: BackgroundIndoor residual spraying of insecticide (IRS) is a key intervention for reducing the burden of malaria infection. Effectiveness and success of this strategy are to a considerable extent dependent on knowledge and practice of the target community regarding the IRS. Iran has entered the malaria elimination phase, and IRS has been considered as the main strategy for malaria vector control. Therefore, this study was conducted to determine the household knowledge and practices about malaria and IRS in Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
10
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 36 publications
5
10
1
Order By: Relevance
“…Taking drug, use of mosquito nets, drain stagnated water (mosquito breeding sites), and house spay with insecticides were the main types of malaria preventive measures frequently reported by the present study participants. This is in line with previous reports from Tanzania [30] and Iran [36].…”
Section: Discussionsupporting
confidence: 94%
“…Taking drug, use of mosquito nets, drain stagnated water (mosquito breeding sites), and house spay with insecticides were the main types of malaria preventive measures frequently reported by the present study participants. This is in line with previous reports from Tanzania [30] and Iran [36].…”
Section: Discussionsupporting
confidence: 94%
“…Eighteen studies reporting IRS coverage were identified in the review [ 27 , 58 , 59 , 66 - 80 ]. Coverage estimates were more commonly obtained through post-campaign household surveys [ 27 , 66 , 69 - 71 , 74 , 76 , 79 , 80 ] than routine IRS program records [ 58 , 59 , 68 , 72 , 73 , 77 ] or study records [ 75 ]. Two studies reported coverage from both household surveys and program records [ 67 , 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…The higher peaks of the larvae and adult species density were observed during April and the smaller peaks during October, after two rainy seasons that create favourable breeding places for anophelines. This implies that these months can be malaria threat times in the study area, which is after one of the two malaria transmission seasons in Bashagard that occurs from April to June and October to December [4].…”
Section: Discussionmentioning
confidence: 99%
“…According to WHO estimation, there were 219 million cases and 435,000 deaths from malaria in 2017 worldwide [3]. It is also one of the most important mosquito-borne diseases in Iran, especially along the international border with Pakistan [4]. Bashagard is one of the malaria foci in this area and indigenous malaria cases are reported from different parts of this county [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation